Elevated Plasma Big Endothelin-1 at Admission Is Associated With Poor Short-Term Outcomes in Patients With Acute Decompensated Heart Failure - Mo, Ran; Yang, Yan-min; Yu, Li-tian; Tan, Hui-qiong; Zhu, Jun (Frontiers in Cardiovascular Medicine, 2021)
Abstract Objective: We aimed to evaluate the association between plasma big endothelin-1 (ET-1) at admission and short-term outcomes in acute decompensated heart failure (ADHF) patients. Methods: In this single-center, retrospective study, a total of 746 acute decompensated heart failure patients were enrolled and divided into three groups according to baseline plasma big ET-1 levels: tertile 1 (<0.43pmol/L, n=250), tertile 2 (between 0.43-0.97pmol/L, n=252) and tertile 3 (>0.97pmol/L, n=244). The primary outcomes were all-cause death, cardiac arrest or utilization of mechanical support devices during hospitalization. Logistic regression analysis and net reclassification improvement approach were applied to assess the predictive power of big ET-1 on short-term outcomes. Results: During hospitalization, 92 (12.3%) adverse events occurred. Aetiology, arterial PH, lactic acid, total bilirubin, serum creatine, serum uric acid, presence of atrial fibrillation and N-terminal pro-B-type natriuretic peptide level positively correlated with plasma big ET-1 level. While systolic blood pressure, serum sodium, hemoglobin, albumin and estimated glomerular filtration rate were in negative correlations. In multivariate logistic regression, tertile 3 comparing to tertile 1 had a 3.68-fold increased risk of adverse outcomes (OR=3.681, 95%CI 1.410-9.606, p=0.008). But such adverse effect did not exist between tertile 2 and tertile 1 (OR=0.953, 95%CI 0.314-2.986, p=0.932). As a continuous variable, big ET-1 level was significantly associated with primary outcome (OR=1.756, 95%CI 1.413-2.183, p<0.001). The C statistic of baseline big ET-1 was 0.66 (95% CI 0.601-0.720, p<0.001). NRI analysis showed that big ET-1 provided additional predictive power when combining it to NT-proBNP (NRI=59.3%, p<0.001). Conclusion: Elevated baseline big ET-1 is an independent predictor of short-term adverse events in ADHF patients and may provide valuable information for risk stratification.